Utilization of Chabot in an Educational System - Beenu; Jindal, Harsh; Kumar, Rakesh; Kushawaha, Meghul Kumar; Kumar, Santosh (Asian Journal of Electrical Sciences, 2021)
Chabot are recently being utilized in a variety of online applications such as education, marketing, supporting systems, cultural heritage and industry from e-commerce to travel. It provides several benefits, such as availability, personalization, etc. Chabot is appeared in very large numbers at the start of the present decade. In a present day, the usage of Chabot is increasing day by day in large scale of the application that is providing better intelligence to the user. In fact, to speed up the assistance these systems are equipped with Chatbots which can interpret the user questions and provide the right answers, in a quick and proper manner. Hence, it is not a part of virtual assistants, but it can be utilized for governments as well as organizations on websites, applications and instant messaging platforms to develop the products, ideas or services. This paper presents the realization of a chatbot in the educational system. In addition, the authors present the historical development, types of chatbot, applications and their future in education sector is described.